Pengaruh Teknologi Terhadap Transformasi Administrasi Publik: Tren dan Tantangan di Era Digital - Romdana, Romdana; Gunawan, Mayang Sari; Oktaviani, There (SENGKUNI Journal (Social Science and Humanities Studies), 2021)
The development of information and communication technologies (ICTs) has been a major driving force in transforming patterns of public administration in different parts of the world. This article analyzes the influence of technology on the transformation of public administration, focusing on the trends and challenges emerging in the digital era. Through an analytical descriptive study, this research covers aspects of technology adoption, operational efficiency, community participation, data management, and the impact of technological globalization in the context of public administration.First, this article describes the trend of technology adoption at the national and local levels. The results show that most governments have integrated technology-based solutions such as e-government and big data to improve administrative efficiency and provide better services to the public.Furthermore, the focus is on the positive effects of technology adoption on operational efficiency and transparency. The implementation of digital systems has helped speed up administrative processes, reduce bureaucracy, and improve information accessibility for the public.Public participation in government decision-making was also highlighted. While technology provides tools to enhance participation, challenges arise regarding the digital divide and people's limited access to technology.Data management and cybersecurity are the next focus. The results show that some government entities face obstacles in managing data, especially in terms of security and privacy. Cybersecurity is a critical issue that needs serious attention to protect the integrity of government information.In a global context, this article discusses how technological globalization affects public administration. International cooperation and information exchange between countries have become easier, but challenges arise in dealing with differences in regulations and administrative standards. Compliance with sustainability principles and energy efficiency were also found to be positive impacts of sustainable technology adoption. Governments that implement green solutions can make a positive contribution to global efforts to safeguard the environment. Nonetheless, the article also highlights some challenges that must be overcome, including the digital divide, cybersecurity risks, and ethical considerations in the use of technology. Taking into account the results of this study, the article concludes by presenting suggestions for further improvements and future research in order to optimize the positive impact of technology on the transformation of public administration in the digital era.